Valuation Analysis Using Fcff And Rv Of Oil And Gas Sub-Sector Companies On Idx 2016-2020 - Muhammad Chalil Gilbran; Riko Hendrawan (JAF (Journal of Accounting and Finance), 2022)
This research aims at examining the intrinsic value of stocks in the oil and gas sectors in 2021. This research used 2016-2020 data to calculate the historical performance of each company, which was projected from 2021-2025 based on three scenarios: optimistic, moderate, and pessimistic. This research employed estimates of the company’s financial behavior in the last five years. The methods used to assess the intrinsic value of these shares were Discounted Cash Flow (DCF) and Relative Valuation (RV). From the results of the research using the DCF method, the following results were obtained: MEDC and ELSA were undervalued in all scenarios, while ESSA was overvalued in all scenarios. With the RV method, the following results were obtained: MEDC, ESSA, and ELSA were undervalued in all scenarios. Overall, MEDC shares were overvalued by -44.7%, ESSA shares were overvalued by 4.6%, ELSA shares were undervalued by -45.6%.